Non-intrusive Monitoring Framework for NoC-based Many-Cores - Dalzotto, Angelo Elias; Borges, Caroline da Silva; Ruaro, Marcelo; Moraes, Fernando Gehm (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2022: Anais do XII Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2022)
Many-core Systems on Chip (MCSoCs) require resource management to achieve scalability at the computation and communication levels. The monitoring infrastructure feeds management tasks with raw data, enabling these tasks to detect behaviors corresponding to constraint violations or a trend that signalizes a future violation. Several works available in the literature use monitoring to apply their management techniques but do not specify how to implement the monitoring framework. We propose a monitoring framework for MCSoCs, with the following features: (i) generic: the infrastructure can carry data related to different monitored features; (ii) monitored data does not disturb NoC flows; and (iii) reduced overhead compared to other monitoring methods. The monitoring framework is loosely coupled to the MCSoC by using a dedicated NoC to carry monitoring and management messages, decoupling data traffic from management traffic. Results adopt the Observe-Decide-Act management method, comparing the proposed monitoring framework to a standard monitoring approach. Results show a reduction in the data NoC traffic (12%), faster management responsiveness to act on deadline violations (up to 77%), and reduced applications execution time (on average 8%).